1996
DOI: 10.1074/jbc.271.46.28753
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine Externalization during CD95-induced Apoptosis of Cells and Cytoplasts Requires ICE/CED-3 Protease Activity

Abstract: Phosphatidylserine (PS), a lipid normally confined to the inner leaflet of the plasma membrane, is exported to the outer plasma membrane leaflet during apoptosis to serve as a trigger for recognition of apoptotic cells by phagocytes. The mechanism of PS export during apoptosis is not known nor is it clear whether the nuclear changes that typify apoptosis contribute in any way to this event. Here, we demonstrate that ligation of the CD95 (Fas/APO-1) molecule on Jurkat cytoplasts induces dramatic PS externalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
211
1
6

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(234 citation statements)
references
References 27 publications
16
211
1
6
Order By: Relevance
“…Previous studies have shown that apoptotic agents promote morphological changes in anucleated cytoplast that resemble characteristics of programmed cell death. 23,24 In platelets, the morphological changes of apoptosis closely resemble those of activation, including PS externalization, microparticle release (i.e., apoptotic bodies), and cell shrinkage. Platelet aging is also characterized by PS externalization; however, it is unclear whether this is reflective of an apoptotic process or an incomplete platelet activation event.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that apoptotic agents promote morphological changes in anucleated cytoplast that resemble characteristics of programmed cell death. 23,24 In platelets, the morphological changes of apoptosis closely resemble those of activation, including PS externalization, microparticle release (i.e., apoptotic bodies), and cell shrinkage. Platelet aging is also characterized by PS externalization; however, it is unclear whether this is reflective of an apoptotic process or an incomplete platelet activation event.…”
Section: Discussionmentioning
confidence: 99%
“…A number of alterations to the composition of the membranes of apoptotic cells have been documented, 54 perhaps the most well known of which is the externalisation of phosphatidylserine on the outer leaflet of the plasma membrane. 55 Although this event is also blocked by inhibition of caspase activity, 56 it remains unclear how phosphatidylserine externalisation or other apoptosis-associated membrane events, is regulated by caspases. In addition to becoming licensed for removal by phagocytes, apoptotic cells may also actively attract the attentions of such cells by secreting molecules with chemotactic properties.…”
Section: How Do Caspases Coordinate Apoptosis?mentioning
confidence: 99%
“…Expression of PS relies on activated caspase 3 in CD95-induced apoptotic cell death, whereas cathepsin B activity is necessary for PS expression in tumor necrosis factor-α-induced caspase-independent cell death 8,9 . Several studies have shown that pathways exist that cause cell surface expression of PS by living cells in specific conditions.…”
Section: Cell Death-independent Ps Externalizationmentioning
confidence: 99%
“…Activated caspases can be detected by western blot with antibodies to cleaved caspase fragments and by flow cytometry using fluorescent probes 17,18 . Caspases are activated early in the apoptotic process before PS expression, so with this method it is possible to detect cells at the onset of apoptosis 8 . Assessment of caspase activity consumes more time than the annexin A5 affinity assay does.…”
Section: Measurement Of Cell Death: a Comparison Of Various Assaysmentioning
confidence: 99%